2022
DOI: 10.31234/osf.io/qnx2v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Value of Social Media Language for the Assessment of Wellbeing: A Systematic Review and Meta-Analysis

Abstract: Wellbeing is an important concept that concerns researchers, policy makers, and the broader general public. The measurement of individuals’ wellbeing levels has predominantly been done through self-reports (e.g., survey questionnaires), which is time-consuming for respondents and costly. Alternatively, wellbeing can be measured in real-time by automatically analysing the language expressed on social media platforms (e.g., Facebook, Twitter, Weibo), through social media language text mining (SMTM). The applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Additionally, they can reveal the degree and manner in which SMTM‐based wellbeing assessments are similar to existing survey measures. Such a fine‐grained comparison (through the networks) between the survey and SMTM‐based wellbeing is important as the correlational convergence shown by the existing literature (Sametoglu et al, 2022) is only based on the aggregate measures of wellbeing (sum of survey items and the predicted wellbeing levels based on all topics features) and does not allow for a comparison between the individual elements (items and language topics) that adds up to overall survey‐ and SMTM‐based wellbeing scores. Therefore, the present study leverages network analysis to provide a detailed comparison between the two methods.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they can reveal the degree and manner in which SMTM‐based wellbeing assessments are similar to existing survey measures. Such a fine‐grained comparison (through the networks) between the survey and SMTM‐based wellbeing is important as the correlational convergence shown by the existing literature (Sametoglu et al, 2022) is only based on the aggregate measures of wellbeing (sum of survey items and the predicted wellbeing levels based on all topics features) and does not allow for a comparison between the individual elements (items and language topics) that adds up to overall survey‐ and SMTM‐based wellbeing scores. Therefore, the present study leverages network analysis to provide a detailed comparison between the two methods.…”
Section: The Present Studymentioning
confidence: 99%
“…This was because the conceptual breadth of the wellbeing survey measures previously used to correlate with SMTM‐based wellbeing scores were mostly limited to hedonic measures of wellbeing (i.e. positive affect or life satisfaction) (Sametoglu et al, 2022). However, contemporary theories of wellbeing (Diener et al, 1985; Keyes et al, 2010; Ryff, 1989) suggest that including both hedonic and eudaimonic wellbeing measures ensure a more comprehensive and detailed picture of an individual's wellbeing levels.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Computational development psychology (Shultz, 2003) has started addressing this gap, identifying markers for emotional and psychological states through text analysis of social media posts (Alharthi et al, 2017;Suh et al, 2021), but the specific focus on parents remains understudied (Westrupp et al, 2022). Furthermore, research (Sametoğlu et al, 2023) has shown that results of research using of social media text mining (SMTM) to assess individuals' well-being correlated with results of studies utilizing self-report measures. Thus, social media posts can be a valid source of data for assessment of parental well-being.…”
Section: Measurement Of Psychological Needs Using Social Media Datamentioning
confidence: 99%
“…Insights could be drawn about how spatial features of places might influence emotional reactions in an online space. Wellbeing can also be measured through social media data text mining, with strong face validity (compared to selfreport data) and convergent validity reported in studies using this type of data (Chen et al, 2014;Sametoglu et al, 2022). Further, social media platforms have a proven ability to change the way people engage with their surroundings and interact with the environment (Gatti & Procentese, 2021), meaning a study on the discourse of natural spaces could draw insights into how different natural environments are being used.…”
Section: Mining Emotions From Textmentioning
confidence: 99%